2021
DOI: 10.1108/aeds-08-2020-0189
|View full text |Cite
|
Sign up to set email alerts
|

Online teaching benefits and challenges during pandemic COVID-19: a comparative study of Pakistan and Indonesia

Abstract: PurposeThe shift from physical class to online classes in the pandemic COVID-19 situation has posited opportunities as well as challenges for teachers and students. The primary purpose of this research is to investigate challenges faced and benefits availed by the teachers at the tertiary level in universities of Pakistan and Indonesia.Design/methodology/approachTo achieve the purpose a mixed-method approach is employed to answer the three research questions of the present study. The quantitative data is obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 20 publications
0
27
0
1
Order By: Relevance
“…According to the majority of the studies, the utilization of ICT for teaching-learning purposes enables teachers and students to stay connected and facilitates learners irrespective of their location and time ( Hussain, 2018 ; Thaheem et al, 2021 ). Teachers also feel comfortable guiding and discussing with their students within or outside the universities through several digital platforms such as WhatsApp, Facebook, and google groups ( Hodgson and Shah, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the majority of the studies, the utilization of ICT for teaching-learning purposes enables teachers and students to stay connected and facilitates learners irrespective of their location and time ( Hussain, 2018 ; Thaheem et al, 2021 ). Teachers also feel comfortable guiding and discussing with their students within or outside the universities through several digital platforms such as WhatsApp, Facebook, and google groups ( Hodgson and Shah, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Amid the COVID-19 crisis, Thaheem et al (2021) carried out a survey to explore the benefits and challenges confronted by teachers in their online instructional practices, where technological challenges, personal constraints, and lack of infrastructure were reported as the major challenges. Similar challenges have been informed by Soomro et al (2020) and Noor et al (2020) , where teachers showed resistance to integrating ICT in their instructional practices due to the lack of adequate infrastructure and technological competencies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study follows a mixed-method approach where we have used both qualitative and quantitative data to reach an in-depth comprehension (Thaheem et al, 2021). Data used in this study have been drawn from a pool of educationists teaching in various HEIs in different parts of India.…”
Section: Procedures and Participantsmentioning
confidence: 99%
“…5 Keeping in mind the recommendations of UNESCO and the prescribed precautionary measures of WHO, many countries observed a paradigm shift from classroom learning to online learning. Educational services through online mode of learning remained available in a large number of countries including Indonesia (Thaheem et al 2021) 6 , India (Mathivanan et al 2021) 7 , Iran (Ahmady, Shahbazi and Heidari 2020 8 ; Younesi 2021 9 ), Saudi Arabia (Oraif and Elyas 2021) 10 , the USA (Asgari et al 2021) 11 , and Germany (König, Jäger-Biela and Glutsch 2020) 12 . Pakistan is no exception in this regard.…”
Section: Al -Aijaz (July -Sep 2021)mentioning
confidence: 99%